A Brief Study on Abortion in Adolescent Girl-Students in Kathmandu Valley - Aryal, Gokarna Raj; Karna, Manoj Kumar (HISAN: Journal of History Association of Nepal, 2023)
Nepali girl-students of the adolescent age group adopt abortion services in justifiable as well as in unethical ways in the verge of career-making in their study and jobs. There are many responsible factors for abortion deed in Nepali society like the negative impact of social media-internet services, globalization, migration, poverty, legal facility for abortion, and so on. This act has adverse effects on their physical health and performance those who adopt this. This research work objectifies the perception and the attitude of such adolescent girl-students in Kathmandu Valley. To ascertain the study accurate, this research work mentions particular data from Kathmandu Valley as primary sources and also some secondary sources from Nepal Demographic Health Survey (NDHS) and others. It further consults Karl Marx's views as well as the psychoanalytic perspective of Georg Wilhelm Friedrich Hegel and Sigmund Freud as the theoretical tools, and the ideas of David Pavon-Cuellar on Marxist-psychoanalytic theory in the relevant context of the data used in this article suitably in the Nepalese context. It follows sharply the quasi-experimental method of writing from the library's text to the internet and also the field work. Historically, the Nepali adolescent girl-students mostly are aware of abortion than the previous time; they have a legal idea about it, its facilities, and its process now. This research shows that there are majority of such Nepali adolescent girl-students in an urban area, even in Kathmandu city, who use abortion knowingly or unknowingly causing their health poor with poor performance and ruining their career so, it is helpful for the stakeholders to work on the issue raised here.